Hidden Wounds of the Inner Child: A Systematic Review on The Psychological Effects of Childhood Trauma in Adulthood - Loama, Rizka Tri; Suwarjo, Suwarjo (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Childhood trauma refers to the lasting impact of adverse experiences during early life that continue to shape behaviour, emotions, and social relationships in adulthood. This study aims to systematically review empirical evidence on how childhood trauma influences adult psychological patterns and identifies effective therapeutic approaches. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, a comprehensive search was conducted across Google Scholar, PubMed, and Scopus. Inclusion criteria were intentionally stringent—focusing only on studies published within the last 15 years, written in English or Indonesian, and directly examining the effects of childhood trauma on adult life. From 967 identified records, only 7 met all inclusion criteria, reflecting the rigorous screening process and ensuring the high relevance and methodological quality of the final selection. The synthesis of findings reveals consistent patterns: adults with unresolved childhood trauma often exhibit low self-esteem, anxiety, depression, and relational difficulties. However, therapeutic approaches emphasizing self-awareness, emotional regulation, and inner child healing demonstrate positive recovery outcomes. Overall, this review underscores that understanding the specific emotional and behavioural patterns rooted in childhood trauma, along with tailored therapeutic interventions, is essential to fostering long-term psychological well-being. Future studies are encouraged to deepen empirical exploration through longitudinal designs.